Risk Factors for Recurrent L4-5 Disc Herniation After Percutaneous Endoscopic Transforaminal Discectomy: A Retrospective Analysis of 654 Cases - Kong M; Xu D; Gao C; Zhu K; Han S; Zhang H; Zhou C; Ma X (Dove Medical Press, 2020)
Meng Kong,1,2,* Derong Xu,1,* Changtong Gao,3 Kai Zhu,1 Shuo Han,1,2 Hao Zhang,1,2 Chuanli Zhou,1 Xuexiao Ma1 1Department of Spinal Surgery, The Affiliated Hospital of Qingdao University, Qing’dao, Shandong Province 266000, People’s Republic of China; 2Department of Medicine, Qingdao University, Qing’dao, Shandong Province 266000, People’s Republic of China; 3Minimally Invasive Interventional Therapy Center, Qingdao Municipal Hospital, Qing’dao, Shandong Province 266000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuexiao Ma Tel +8618661807895Email ma_xuexiao@126.comChuanli ZhouDepartment of Spinal Surgery, The Affiliated Hospital of Qingdao University, No. 59, Hai Er Road, Qing’dao, Shandong Province 266000, People’s Republic of ChinaTel +86 18661809796Email justin_5257@hotmail.comBackground: Percutaneous endoscopic lumbar discectomy (PELD) is an increasingly applied minimally invasive procedure that has several advantages in the treatment of lumbar disc herniation (LDH). However, recurrent LDH (rLDH) has become a concerning postoperative complication. It remains difficult to establish a consensus and draw reliable conclusions regarding the risk factors for rLDH.Purpose: This retrospective study aimed to investigate the risk factors associated with rLDH at the L4-5 level after percutaneous endoscopic transforaminal discectomy (PETD).Methods: A total of 654 patients who underwent the PETD procedure at the L4-5 level from October 2013 to January 2020 were divided into a recurrence (R) group (n=46) and a nonrecurrence (N) group (n=608). Demographic and clinical data and imaging parameters were collected and analyzed using univariate and multiple regression analyses.Results: The current study found a 7% rate of rLDH at the L4/5 level after successful PETD. Univariate analysis showed that older age, high BMI, diabetes mellitus history, smoking, large physical load intensity, moderate disc degeneration, small muscle–disc ratio (M/D), more fat infiltration, large sagittal range of motion (sROM), scoliosis, small disc height index (DHI), small intervertebral space angle (ISA), and small lumbar lordosis (LL) were potential risk factors (P < 0.10) for LDH recurrence after PETD at the L4-5 level. Multivariate analysis suggested that high BMI, large physical load intensity, moderate disc degeneration, small M/D, more fat infiltration, large sROM, small ISA, and small LL were independent significant risk factors for recurrence of LDH after PETD.Conclusion: Consideration of disc degeneration, M/D, fat infiltration of the paravertebral muscles, sROM, ISA, LL, BMI, and physical load intensity prior to surgical intervention may contribute to the prevention of rLDH following PETD and lead to a more satisfactory operative outcome and the development of a reasonable rehabilitation program after discharge.Keywords: percutaneous endoscopic transforaminal discectomy, recurrent LDH, risk factor